2022
DOI: 10.1093/ehjci/jeac217
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of myocardial perfusion imaging by 82-rubidium positron emission tomography in male and female patients with angina and no perfusion defects

Abstract: Aims Myocardial perfusion imaging with 82-rubidium positron emission tomography (82Rb-PET) is increasingly used to assess stable coronary artery disease (CAD). We aimed to evaluate the prognostic value of 82Rb-PET-derived parameters in patients with symptoms suggestive of CAD but no significant reversible or irreversible perfusion defects. Methods and results Among 3726 consecutive patients suspected of stable CAD who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Six studies, encompassing 9,507 subjects, presented HRs for mortality [5, 28, 31, 33, 34, 37]. The median follow-up period ranged from 1.6 to 12.5 years.…”
Section: Quantitative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies, encompassing 9,507 subjects, presented HRs for mortality [5, 28, 31, 33, 34, 37]. The median follow-up period ranged from 1.6 to 12.5 years.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…In this study, we expanded on previous meta-analysis [10,11] by including more recent studies [18,19,25,26,[31][32][33][34][35][36][37][38][39][40]. We have expanded our study population to include a greater number of Asian populations, such as those from China and Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Several cardiovascular imaging techniques have been proposed to assess microvascular dysfunction (Mathew et al 2020 ), including cardiac PET/CT. Some studies reported that MFR < 2 has a significant prognostic value in symptomatic women with non-obstructive CAD (Gulati et al 2009 ) as well as in patients without perfusion defect (Rauf et al 2022 ). Considering patients with no obstructive epicardial CAD, SVD patients represented 38/214 patients (17.8%), which is quite low compared to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Considering patients with no obstructive epicardial CAD, SVD patients represented 38/214 patients (17.8%), which is quite low compared to previous reports. Indeed, Rauf et al ( 2022 ) recently reported in a large population that 27.9% of the patients ( N = 2175) with no significant perfusion defect on 82 Rb cardiac PET had a MFR < 2, while other authors even reported higher SVD prevalence up to 54% in patients without perfusion defect (Murthy et al 2014 ). While the authors did not report angiography results, they considered that low calcium score was likely indicative of low risk of triple-vessel CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus all [ 15 O]H 2 O PET scans were performed during the startup period. The center has a high-throughput with around 1,500 heart PET examinations per year 16 and during the startup period, a number of exams were co-reviewed by experts from Turku PET Centre to ensure quality. To increase the likelihood of ischemia in the cohort, we included patients with typical anginal chest pain and with at least one of the following risk factors: a family history of cardiac disease (< 55 years for male and < 65 years for female family members), smoking, diabetes, hypertension, BMI > 30 or hyperlipidemia.…”
Section: Methodsmentioning
confidence: 99%